2018
DOI: 10.3389/fmicb.2018.00866
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic and Morphological Change Analyses of Staphylococcus aureus During Resuscitation From Prolonged Freezing

Abstract: When frozen, Staphylococcus aureus survives in a sublethally injured state. However, S. aureus can recover at a suitable temperature, which poses a threat to food safety. To elucidate the resuscitation mechanism of freezing survived S. aureus, we used cells stored at -18°C for 90 days as controls. After resuscitating the survived cells at 37°C, the viable cell numbers were determined on tryptic soy agar with 0.6% yeast extract (TSAYE), and the non-injured-cell numbers were determined on TSAYE supplemented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…6b) in accordance to the results reported by Wieland et al (Wieland et al, 1994), who found a 50% lower concentration of STX compared with 4.4'-DNP after 12 hours of growth. The lower presence of xanthophylls at the initial growth stage is in line with proteomic studies of S. aureus, which also observed significant differences in protein expression levels between resuscitating and freezing survived cells (Suo et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…6b) in accordance to the results reported by Wieland et al (Wieland et al, 1994), who found a 50% lower concentration of STX compared with 4.4'-DNP after 12 hours of growth. The lower presence of xanthophylls at the initial growth stage is in line with proteomic studies of S. aureus, which also observed significant differences in protein expression levels between resuscitating and freezing survived cells (Suo et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…The rest of the procedure was as described previously by Suo et al. (Suo et al., 2018). Morphological alterations of the bacteria were observed and photographed using a Quanta 200 FEG environmental scanning electron microscope (FEI Co., Inc., Hillsboro, OR, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The sample was then digested to produce the final trypsinized peptide sample as described previously by Suo et al. (Suo et al., 2018). The fraction was separated by Easy-nLC 1000 system (Thermo Fisher Scientific, MA, USA) and analyzed by Q-Exactive mass spectrometer (Thermo Fisher Scientific, MA, USA) equipped with an online nano-electrospray ion source.…”
Section: Methodsmentioning
confidence: 99%
“…Certainly, there will be diverse challenges to identify pathogens collected from food and/or environmental samples. Due to environmental stress pathogens may show some modification both in their morphology 45,46 and elemental informations. Addressing this issue requires conducting this kind of research continuously for other types of standard reference pathogens as well as pathogens collected from food and/or environment and obtaining a standard quality of EDX spectra for the pathogens that we did not study for the current research.…”
Section: Sem-edx Measurement Without Using Any Fixative Reagent and Mmentioning
confidence: 99%